Resistant Cultivars for Florida Tomato and Pepper Production - Gene McAvoy (EDIS)
IPM-205, a 2-page illustrated fact sheet by G. McAvoy, is part of the Grower’s IPM Guide for Florida Tomato and Pepper Production. It discusses disease resistance in general, limitations, and resistance in tomato and pepper varieties. Published by the UF Department of Entomology and Nematology, January 2008.